1966
DOI: 10.1246/bcsj.39.1468
|View full text |Cite
|
Sign up to set email alerts
|

The Crystal Structure of Succinonitrilo-disilver Nitrate, 2AgNO3·NC(CH2)2CN

Abstract: The structure of 2AgNO3•ENC(CH2)2CN has been determined by X-ray analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1967
1967
1989
1989

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Kubota and coworkers 4 demonstrated that polymeric structures arose when tin or titanium tetrachloride coordinate with dinitriles where the latter act as a bridging ligand. Succinonitrile assumes trans conformation in these compounds as well as in compounds with silver 14 and copper 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Kubota and coworkers 4 demonstrated that polymeric structures arose when tin or titanium tetrachloride coordinate with dinitriles where the latter act as a bridging ligand. Succinonitrile assumes trans conformation in these compounds as well as in compounds with silver 14 and copper 15 .…”
Section: Introductionmentioning
confidence: 99%